Towards Achieving Sustainable Development Goals: An Appraisal of 10-3-4 System of Education in Nigeria - Abel Ebiega Enokela (Sociometry Journal of Social Science, Art and Humanity, 2021)
This chapter appraised the 10-3-4 system of education in Nigeria in line with the sustainable development goals (SDGs) of UNO and vision 2030. Particular emphasis was placed on the SDG 4 whose focus is on equitable and qualitative education for all irrespective of background, religion, race or disability. The goal of sustainable development education is to raise global citizens that can fit into our multicultural world with appropriate knowledge, skills and competences that could align with the demands of immediate localities and the world as a whole. Nigeria’s current national policy on education (FRN, 2013) lays emphasis on compulsory basic education for all. However, findings reveal an abysmal implementation of the scheme, culminating in a high number of out-of-school children. The post basic and tertiary education are also in pathetic conditions as they have failed markedly to address issues of sustainable development, and pave way for unemployment rate to continue to escalate. The study through secondary data, observed poor implementation of the policy, inadequate funding, corruption, unqualified personnel among others as the banes of sustainable education in the country. Nigeria’s government should take measures to revive the educational sector in order to meet up with the sustainable development goals. The study recommends an overhaul of the nation’s educational system.